AB0683 Treatment with statins in patients studied by fdg-pet/ct for possible large vessel vasculitis is associated with a low vascular score. (12th June 2018) - Cimmino, M.A.; Iannuzzi, F.; Camellino, D.; Morbelli, S.; Pizzorni, C.; Cutolo, M.; Sambuceti, G.
Abstract : Background: Polymyalgia rheumatica (PMR), giant cell arteritis (GCA), and fever of unknown origin (FUO) may show large vessel vasculitis (LVV) when studied with FDG-PET/CT. Statins, widely used to lower cholesterol concentrations, have shown anti-inflammatory activity in both the atherosclerotic plaque and in rheumatoid arthritis. Objectives: To test the hypothesis that the concomitant treatment with statins induces a low uptake of the vessels in patients with PMR, FUO and GCA. Methods: Consecutive patients with a diagnosis of PMR, GCA or FUO underwent a thorough clinical examination, including drug history, and a PET/CT scan. Arterial uptake of FDG was scored relative to liver uptake as 0=no uptake present, 1=lower than liver uptake, 2=similar to liver uptake, 3=higher than liver uptake. The values of each district were summed to obtain a total vascular score (TVS). A further semi-quantitative analysis of FDG uptake was carried out, drawing regions of interest (ROIs) on the theoretical arterial wall and within the left ventricular chamber (blood-pool, BP). Arterial FDG uptake was quantified by calculating the mean standardised uptake value (SUV) within each ROI and the results expressed as the ratio between mean SUV value of each ROI and BP ROI (SUV/BP). Results: 129 patients were included, 87 women, with median age of 74 years (range 50–92). 95 patients were diagnosed with PMR, 13 with GCA, 16 with both PMR and GCA and 5 patients presented with FUO. 37/129 patients (28.7%) were assuming glucocorticoids (GC) at the time of examination. The mean interval between onset of symptoms and PET/CT was 85 days (range 4–1957 days). LVV was present in 75 patients (58.2%) when a cut-off ≥2 was used and 32 patients (24.8%) had a score of 3. Twenty/129 patients (15.5%) were treated with statins for hypercholesterolemia. The median TVS was significantly lower in these patients when compared with those not treated with statins (8 [range 1–27] vs. 12 [range 0–42], p=0.02). This difference was present at the ascending aorta (p=0.017), the aortic arch (p=0.023), and the femoral arteries (p=0.025). The analysis of SUV was not significant (p=0.45). As expected, the arterial calcium load, corresponding to the extent of vessel calcification, was higher in patients treated with statins (14 [range 2–35] vs. 8 [range 0–35]; p=0.012). However, calcium load did not correlate with the TVS, whereas it inversely correlated with SUVs (p=0.03). At multiple regression, assumption of statins was not predicted by sex, type of diagnosis, GC treatment or presence of LVV at PET/CT. Only age predicted statin therapy (p=0.04), but age was not associated with LVV (p=0.23). Among clinical features, only fever was significantly less frequent in patients treated with statins (p=0.03). Conclusions: With the limits of an observational retrospective study, our data suggest that treatment with statins may lower arterial uptake in patients studied for LVV. This finding was seen using the theoretically more subjective TVS but not with SUV analysis. We feel that the latter is more easily influenced by the presence of calcific plaques, as suggested by its inverse correlation with arterial calcium load. The role of statins in tempering arterial inflammation deserves further studies. Disclosure of Interest: None declared